A Time-Course-Based Estimation of the Human Medial Olivocochlear Reflex Function Using Clicks - Boothalingam, Sriram; Goodman, Shawn S.; MacCrae, Hilary; Dhar, Sumitrajit (Frontiers in Neuroscience, 2021)
The auditory efferent system, especially the medial olivocochlear reflex (MOCR), is implicated in both typical auditory processing and in auditory disorders in animal models. Despite the significant strides in both basic and translational research on the MOCR, its clinical applicability remains under-utilized in humans due to the lack of a recommended clinical method. Conventional tests employ broadband noise in one ear while monitoring change in otoacoustic emissions (OAEs) in the other ear to index efferent activity. These methods, (1) can only assay the contralateral MOCR pathway and (2) are unable to extract the kinetics of the reflexes. We have developed a method that re-purposes the same OAE-evoking click-train to also concurrently elicit bilateral MOCR activity. Data from click-train presentations at 80 dB peSPL at 62.5 Hz in 13 young normal-hearing adults demonstrate the feasibility of our method. Mean MOCR magnitude (1.7 dB) and activation time-constant (0.2 s) are consistent with prior MOCR reports. The data also suggest several advantages of this method including, (1) the ability to monitor MEMR, (2) obtain both magnitude and kinetics (time constants) of the MOCR, (3) visual and statistical confirmation of MOCR activation.